Free Trehalose Accumulation in Dormant Mycobacterium smegmatis Cells and Its Breakdown in Early Resuscitation Phase - Shleeva, Margarita O.; Trutneva, Kseniya A.; Demina, Galina R.; Zinin, Alexander I.; Sorokoumova, Galina M.; Laptinskaya, Polina K.; Shumkova, Ekaterina S.; Kaprelyants, Arseny S. (Frontiers in Microbiology, 2017)
Under gradual acidification of growth medium resulting in the formation of dormant Mycobacterium smegmatis, a significant accumulation of free trehalose in dormant cells was observed. According to 1H- and 13C-NMR spectroscopy up to 64% of total organic substances in the dormant cell extract was represented by trehalose whilst the trehalose content in an extract of active cells taken from early stationary phase was not more than 15%. Trehalose biosynthesis during transition to the dormant state is provided by activation of genes involved in the OtsA-OtsB and TreY-TreZ pathways (according to RT-PCR). Varying the concentration of free trehalose in dormant cells by expression of MSMEG_4535 coding for trehalase we found that cell viability depends on trehalose level: cells with a high amount of trehalose survive much better than cells with a low amount. Upon resuscitation of dormant M. smegmatis, a decrease of free trehalose and an increase in glucose concentration occurred in the early period of resuscitation (after 2 h). Evidently, breakdown of trehalose by trehalase takes place at this time as a transient increase in trehalase activity was observed between 1 and 3 h of resuscitation. Activation of trehalase was not due to de novo biosynthesis but because of self-activation of the enzyme from the inactive state in dormant cells. Because even a low concentration of ATP (2 mM) prevents self-activation of trehalase in vitro and after activation the enzyme is still sensitive to ATP we suggest that the transient character of trehalase activation in cells is due to variation in intracellular ATP concentration found in the early resuscitation period. The negative influence of the trehalase inhibitor validamycin A on the resuscitation of dormant cells proves the importance of trehalase for resuscitation. These experiments demonstrate the significance of free trehalose accumulation for the maintenance of dormant mycobacterial viability and the involvement of trehalose breakdown in early events leading to cell reactivation similar to yeast and fungal spores.